2014
DOI: 10.3390/molecules190811385
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antiplatelet Activities of Plasma Are Conserved Across Twelve Mammalian Species

Abstract: Human plasma inhibits arachidonic acid metabolism and platelet aggregation. This helps human form a haemostatic control system that prevents the progress of certain aggregatory or inflammatory reactions. Whether this property of plasma is unique to human or extends to other species is not well known. It is speculated that this protective ability of plasma remains evolutionarily conserved in different mammals. In order to confirm this, the effect of plasma from 12 different mammalian species was investigated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…However, MD-Aq was not effective against collagen and ADPinduced platelet aggregation. Similar pharmacological effects of medicinal plants have been reported previously (Ahmed, Gul, Idris, et al 2014) (Gul et al 2013). It has been reported that apples and other healthy fruits and vegetables offer pharmacological benefits through various mechanisms such as scavenging free radicals, inhibiting free radical production, and enhancing the synthesis of antioxidant enzymes to protect the body from damage (Fernandez-Panchon et al 2008, Halliwell, Rafter, and Jenner 2005, Balasundram, Sundram, and Samman 2006.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, MD-Aq was not effective against collagen and ADPinduced platelet aggregation. Similar pharmacological effects of medicinal plants have been reported previously (Ahmed, Gul, Idris, et al 2014) (Gul et al 2013). It has been reported that apples and other healthy fruits and vegetables offer pharmacological benefits through various mechanisms such as scavenging free radicals, inhibiting free radical production, and enhancing the synthesis of antioxidant enzymes to protect the body from damage (Fernandez-Panchon et al 2008, Halliwell, Rafter, and Jenner 2005, Balasundram, Sundram, and Samman 2006.…”
Section: Discussionsupporting
confidence: 77%
“…Human plasma was used as a sample. The assay was done as explained by Ahmed and associates (Ahmed, Gul, Idris, et al 2014). All the kit chemicals, MD-Aq, and finally, the substrate were added sequentially to create the reaction mixture.…”
Section: Measurement Of Total Antioxidant Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…One very common initial point is median MV of adjacent blocks in the current frame which has been used in many predictive algorithms [20]. In H.264/AVC standard, after finishing the ME process the encoder needs to calculate this spatial median MV for other modules any ways, hence using that in initial step of ME does not add any extra calculation to the process.…”
Section: Chapter4 Predictive Search Algorithmsmentioning
confidence: 99%
“…Methanolic extract of Acacia leucophloea bark (Mimosaceae) significantly inhibited ADP-induced human platelet aggregation (Imran et al, 2012). The aqueous fraction of Cinnamomum tamala (Lauraceae) showed potent inhibition against ADP-induced aggregation but was only partially active against collagen-induced aggregation (Ahmed et al, 2014). Crude extract of Rhynchosia reniformis (Fabaceae) potently blocked ADP-stimulated aggregation of platelets (Ahmad et al, 2011).…”
Section: Anti-adp Extracts/fractionsmentioning
confidence: 99%